(3cJGH GdYQhSs - (3Gdbej, CHh eMeO, , LYaQ Hf CMeO Hf Ydj, J (B381 (3g`s ((3YHO GdMejO Hf eMeO GdCUagGfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3SCdJ CWGd Gddg HbGAc gd NU jhe GdLeYI HYHGOI Shi CjGe GdCSHhY GYde Ydec Gddg GdNjQGJ(B...s
(3BNQgG (B:s
(3fgi QShd Gddg Yf GdcdGe jhe GdLeYI hGdEeGe jNWH (B... (3Ke bGd(B: (3EPG bGd GdQLd jhe GdLeYI eg adG UdGI dg(B.s
(3JHUQI GdYfhGf (B:s
(3GdYQhS aj aVGFd jhe GdLeYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI; HQbe(B: 1837s
(3GdPQjYI; HQbe(B: 2179s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs